TITLE: THE PHYSICAL EDUCATION AND VALUES IT PROMOTES: INTERNATIONAL PERSPECTIVE (Fiep Bulletin - online, 2020)
The purpose of this study was to carry out a documentary exploratory analysis of research on values ??in the field of physical education; it is based on a search for what has been written at the international level to strengthen strategies for teaching values, and contribute to a better understanding of the educational field at the national level.Empirical research was found that raises student satisfaction in the physical education class, perception of teachers; behavior, and preference for the programs didactic content, as the topics of greatest interest. The papers emphasize the perception of personal and social values ??in the interaction of the physical education class. The values ??of respect, sociability, cooperation, fun, hedonism, health, self-realization, social achievement and power, fair play and sportsmanship are highlighted. The social imaginaries of the body and the meanings of the EF class revolve between the functionalist and sporty paradigm of today's lifestyles. The educational work of the teacher, the mastery of his subject and his behavior are criticized as decisive elements for the active participation of the student in class. The preference for the subject decreases as age progresses, with a higher percentage in girls than in boys.Postulates emerge that orient the theoretical discussion and practices of physical education towards a pedagogical and didactic orientation that enhances values ??and attitudes.